ANALISA KUALITAS DAN SUMBERDAYA BATUBARA LAPANGAN X, PT. BUKIT ASAM (PERSERO) TBK., TANJUNG ENIM, SUMATERA SELATAN - Dian Agus Widiarso; Faiq Nirmala (JURNAL GEOMINERBA (JURNAL GEOLOGI, MINERAL DAN BATUBARA), 2022)
Exploration activities are needed to find areas that have coal potential. The research area is an area that has not been mined yet. The purpose of this study is to determine the distribution of the coal in the area of research and analysis resource calculation, rank coal, coal and quality in the research area. The method used is to do the mapping to determine the distribution of coal. coal quality analysis is based on the proximate analysis and calculation of coal resources by using software Minescape 4118. seam A1 has measured resources amounted to 28.6 million tons, designated amounted to 27.8 million tons and 26.1 million tons of inferred. seam A2 has measured resources amounted to 58.2 million tons, designated amounted to 39.6 million tons and 33.5 million tons of inferred. seam B1 has measured resources amounted to 62.5 million tons, designated amounted to 36.2 million tons and 35.8 million tons of inferred. seam B2 has measured resources amounted to 7.89 million tons, designated amounted to 8.63million tons and 9.50 million tons of inferred. seam C has measured resources amounted to 67.8 million tons, designated amounted to 33.1 million tons, and amounted to 37.5 million tonnes inferred. total moisture values obtained tend to be low. Sulfur high value on the seam B1 and C are high influenced by the presence of sea water. The calorific value of the highest in the area of research is on the seam of seam C because C is the oldest seam.